Kennicutt-Schmidt Law in the Central Region of NGC 4321 as Seen by ALMA - Azeez, J.H.; Hwang, C.Y.; Abidin, Z.Z.; Ibrahim, Z.A. (Nature Publishing Group, 2016)
We present the Atacama Large Millimeter/Sub-millimeter Array (ALMA) cycle-0 science verification data of the CO(1-0) line emission in the central region of NGC 4321 (also known as M100) at the distance of 17.1 Mpc and VLA, L-band data of HI of the same galaxy. We have drawn the center area of M100 in the 12CO(J = 1-0) line with the resolution of (3.87″ × 2.53″) as viewed by ALMA, along with HI and Spitzer 8 and 3.6 μm data. The relationship between the surface density of molecular gas mass ΣH2 and that of star formation rate ΣSFR has been investigated, in addition to the relationship between the surface density of the neutral atomic hydrogen mass and that of ΣSFR (Kennicutt-Schmidt law) in this galaxy with a high spatial resolution. The results indicate that a significant correlation exists between the SFR surface density and the molecular gas mass density in the ∼2 kpc region. The power-law index has been determined for three regions: center, upper and lower arms. The value of this index in the center region is 1.13, which follows the traditional (K-S) law and indicates that the molecular gas is affected by star formation.